American federalism : a concise introduction - Gerston, Larry N. (M.E. Sharpe, 2007)
Understanding federalism is central to the study of democratic government in the United States. This book examines the historical and philosophical underpinnings of federalism; and the ways in which institutional political power is both diffused and concentrated in the United States.